A blended group intervention to promote social connectedness and wellbeing among international university students: an exploratory study - Cipolletta, Sabrina; Tedoldi, Ilaria; Tomaino, Silvia Caterina Maria (Frontiers in Psychology, 2024)
Loneliness is a prevalent issue among international university students, often exacerbated by cultural and linguistic barriers. This pilot study aims to assess the feasibility, acceptability and impact of a blended intervention to promote international students' social connectedness and well-being. A sample of 49 international students from the University of Padua (Italy) was recruited. The study followed the methodology of a non-randomized controlled trial comparing a blended intervention (comprising group activities and online self-help materials) with two other active conditions (selfhelp only and peer-to-peer interventions) and a control condition at two times (baseline and at 8 weeks). Participants completed a survey to assess their satisfaction with the interventions, changes in their interactions and wellbeing. They also filled in some questionnaires to measure anxiety, depression, perceived social support, loneliness and satisfaction with life. A mixed-method analysis was conducted. Results showed that interventions involving in-person activities had significant advantages over self-help intervention in terms of interaction improvement and a higher number of relationships. Participants perceived self-help materials as more relevant, satisfactory, and functional within the blended group compared to the self-help group. Contrary to the control group, the blended and peer-to-peer groups reported lower scores on the standardized measures of loneliness, anxiety, and depression, and higher scores on satisfaction with life, collected pre-and post-intervention. The thematic analysis of the answers to the open-ended questions showed that in-person group activities provided the opportunity to compare themselves with peers and have a direct experience of new social connections. The findings highlight the importance of translating insights from self-help materials into active and direct social experiences, to reduce loneliness through the emergence of new perspectives and shared meaning making.